Apply Molecular Method To Diagnosis A Very Rare Bone Primary Myoepithelial Tumor: A Case Report. (28th October 2020) - Chen, F; Syed, H
Abstract: Introduction/Objective: A 38-year-old female without a history of trauma and malignancy presented with left knee pain and swelling for two weeks. MRI and PET scan find a left knee mass arising from the bone along the medial metaphysis of the distal femur. She underwent femur resection, and the specimen was sent for pathology evaluation. Methods: Grossly, the cut surface of the sample revealed a 4.5 x 2 cm area of hemorrhagic softening of the bone with adjacent soft tissue nodules. Microscopically, the tumor showed biphasic or multiphase morphologic features, prominently presented with areas showing well-differentiated epithelial features and other areas with spindling and sheets of tumor cells. Areas suspicious for a vascular invasion were seen at the periphery of the soft tissue extension of the tumor. Immunohistochemistry stains showed the tumor cells are positive for vimentin, AE1/3, EMA, CK7, CK19, GATA3, and BRST2; and are negative for S100, HMB45, GFAP, Calponin, CDX2, PAX8, WT1, P63, CD34, and ER. The molecular test showed positive for the ESWR1 gene but negative for SYT gene translocation. Results: A diagnosis of primary myoepithelial carcinoma of bone extension into surrounding soft tissue was made. Conclusion: The most challenging differential diagnosis for this case is metastatic breast cancer. Many of the positive epithelial stains distinctly highlight the epithelial featured geographic areas sparing the background spindled stroma. The positive staining of GATA3 and BRST2, two commonly used breast linage markers, is unusual and not known in myoepithelial carcinoma. In light of the EWSR1 positive and SYT FISH negative results, combined with the morphologic features, locations as well as negative PET scan against its breast origins. Although many myoepithelial markers, such as S100, Calponin, P63, and GFAP were negative, make this case very unique. The molecular diagnosis is the mainstay for this final diagnosis.